Assessing the Potential of Najm al-Din al-Tufi’s Maṣlaḥah for Islamic Legal Reform - Riza, Achmad Kemal; Bilhaq, Ahmad Razan (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2025)
This paper discusses the thoughts of Najm al-Din al-Tufi (1277–1316 AD), a Hanbali scholar who was known to be radical in carrying out the concept of maṣlaḥah. This research is a normative and textual approach. Data collection is carried out through literature review, and it was analyzed descriptively. This article finds that al-Tufi places maṣlaḥah as the main postulate in the determination of the law, even in certain cases it can surpass nas and ijma'. This thought departs from his commentary on the hadis lā ḍarar wa lā ḍirār, which, according to him, affirms the principle of the elimination of harm and the maintenance of benefits. He defines maṣlaḥah broadly, dividing it into two domains: worship and muqaddarāt, which are subject to nas, and mu'āmalāt, which is entirely subject to human welfare. Within this framework, al-Tufi developed the methods of tarjīḥ and bayān to resolve the contradiction in the postulate by prioritizing maṣlaḥah. His thoughts sparked controversy; some scholars accuse him of ignoring the authority of the text, while modern thinkers see it as a progressive bid to renew Islamic law. Although limited only to the realm of mu'āmalāt, the idea of al-Tufi is still relevant in responding to contemporary legal problems that are not explicitly accommodated in nas or ijma'.